2012
DOI: 10.1002/pola.26373
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl‐terminated liquid‐crystalline dendrimers based on dendritic polyols and their siloxane‐based elastomers

Abstract: A new series of side-chain liquid-crystalline dendrimers (LCDs) by grafting vinyl-terminated phenyl benzoatebased promesogens to a novel polypropyleneimine-derived dendritic polyols are reported. Polarized optical microscopy and X-ray diffraction studies show that both the compounds display a smectic-A (SmA) mesophase. The second-generation dendrimer bearing eight-branched promesogens exhibits a more stable SmA mesophase with a wide mesomorphic temperature range. It is demonstrated that ''promoting groups'' in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…After 153 days (Figure S3e in the Supporting Information), the POM observation barely detected the presence of optically anisotropic domains after changing the brightness and contrast of the image. Nevertheless, the liquid crystallinity of those samples was still maintained because the wide-angle XRD patterns (Figure S4 in the Supporting Information) only showed two diffuse maxima at around 2θ = 13°and 18°, which originate from the interchain packing of siloxane and hydrocarbon chain segments, respectively, [41][42][43] suggesting no presence of long-range ordering in the direction perpendicular to the molecular long axis.…”
Section: Resultsmentioning
confidence: 99%
“…After 153 days (Figure S3e in the Supporting Information), the POM observation barely detected the presence of optically anisotropic domains after changing the brightness and contrast of the image. Nevertheless, the liquid crystallinity of those samples was still maintained because the wide-angle XRD patterns (Figure S4 in the Supporting Information) only showed two diffuse maxima at around 2θ = 13°and 18°, which originate from the interchain packing of siloxane and hydrocarbon chain segments, respectively, [41][42][43] suggesting no presence of long-range ordering in the direction perpendicular to the molecular long axis.…”
Section: Resultsmentioning
confidence: 99%
“…J. Sun [30] reported the preparation of vinyl-terminated liquid crystalline dendrimers based on dendritic polyols and their siloxane-based elastomers. This is quite an unexplored topic of research up to now, and therefore, the properties found for these materials open a broad field of possibilities for further investigation.…”
Section: Introductionmentioning
confidence: 99%